The Influence of Relationship Quality and Switching Costs on Customer Loyalty in the Malaysian Hotel Industry - Abdul-Rahman, M.; Kamarulzaman, Y. (Elsevier, 2012)
The intense competition among hotels in Malaysia means that there is a larger demand for service outsourcing. Hotels are now exposed to a wider choice of service providers that are willing to provide services. As a result, hotel managements are more inclined to switch to other service providers if the current service providers are unsatisfactory. This paper aims to investigate the effect of relationship quality and switching costs on business customer loyalty from the customers’ perspective in the context of hotel service outsourcing. This study is important considering the economic advantages of retaining current customers as opposed to searching for new customers. Partial Least Squares was adopted as the data analysis methodology. Results of the study show that relationship quality positively and significantly influences customer loyalty. However, switching costs does not influence customer loyalty.